The effect of calorie-restriction along with thylakoid membranes of spinach on the gut-brain Axis Pathway and oxidative stress biomarkers in obese women with polycystic ovary syndrome: a Randomized, Double-blind, placebo-controlled clinical trial - Negin Nikrad; Mahdieh Abbasalizad Farhangi; Fatemeh Pourteymour Fard Tabrizi; Maryam Vaezi; Ata Mahmoudpour; Mehran Mesgari-Abbasi (BMC, 2023)
Abstract Background Women with polycystic ovary syndrome (PCOS) have higher intestinal mucosal permeability, leading to the lipopolysaccharide (LPS) leakage and endotoxemia. This, in turn, leads to oxidative stress (OS) and neuro-inflammation caused by the gut-brain axis, affecting the neurotrophic factors levels such as brain-derived neurotrophic factor (BDNF) and S100 calcium-binding protein B (S100 B) levels. In this study, it was hypothesized that the thylakoid membranes of spinach supplementation along with a hypocaloric diet may have improved the LPS levels, neurotrophic factors, and OS in PCOS patients. Methods In this double-blind, randomized, placebo-controlled, and clinical trial, 48 women with obesity and diagnosed with PCOS based on Rotterdam criteria were randomly assigned to thylakoid (N = 21) and placebo groups (N = 23). A personalized hypocaloric diet with 500 calories less than the total energy expenditure was prescribed to all patients. The participants were daily supplemented with either a 5 g/day thylakoid-rich spinach extract or a placebo (5 g cornstarch) for 12 weeks along with a prescribed low-calorie diet. Anthropometric measurements and biochemical parameters were assessed at baseline and after the 12-week intervention. Results A statistically significant decrease in the LPS levels (P < 0.001) and an increase in the BDNF levels (P < 0.001) were recorded for the participants receiving the oral thylakoid supplements and a low-calorie diet. Furthermore, significant decreases were observed in fasting blood glucose, insulin, homeostatic model of assessment for insulin resistance, free testosterone index, and follicle-stimulating hormone / luteinizing hormone ratio in both groups (P < 0.05). No significant differences were detected between the two groups regarding the changes in malondialdehyde, catalase, total antioxidant capacity, and S100B levels (P > 0.05). Conclusions In sum, the thylakoid membranes of spinach supplemented with a hypocaloric diet reduced the LPS levels, increased the BDNF levels, and improved the glycemic profile and sex-hormone levels; however, they had no effects on the OS markers levels after 12 weeks of intervention.